2013
DOI: 10.1007/s00259-013-2493-9
|View full text |Cite|
|
Sign up to set email alerts
|

Comparative study of the safety of regadenoson between patients with mild/moderate chronic obstructive pulmonary disease and asthma

Abstract: This study showed a good safety profile in our series of COPD and asthma patients undergoing MPI. Regadenoson was well tolerated by all patients, with dyspnoea, headache and feeling hot showing differences between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Similar results have been seen in observational studies in patients with lung disease undergoing MPI for evaluation of CAD. 14,15 In these studies including 228 and 116 patients, no clinically apparent bronchospasm or exacerbation of lung disease was observed immediately after regadenoson infusion. In all of the above mentioned studies, the severity of the lung diseases has been limited to mild or moderate in the majority of patients.…”
mentioning
confidence: 86%
“…Similar results have been seen in observational studies in patients with lung disease undergoing MPI for evaluation of CAD. 14,15 In these studies including 228 and 116 patients, no clinically apparent bronchospasm or exacerbation of lung disease was observed immediately after regadenoson infusion. In all of the above mentioned studies, the severity of the lung diseases has been limited to mild or moderate in the majority of patients.…”
mentioning
confidence: 86%
“…2 Dynamic exercise is preferred for inducing coronary hyperemia during a cardiac stress test; however, pharmacological agents may be used in patients with contraindications or intolerance to exercise stress testing. 3 The American Society of Nuclear Cardiology (ASNC) imaging guidelines for single-photon emission computed tomography (SPECT) nuclear cardiology procedures: stress, protocols, and tracers (2016) discuss 4 agents for use in pharmacological stress testing: adenosine, regadenoson, dipyridamole, and dobutamine. 2 The first 3 agents are coronary vasodilators.…”
Section: Cardiac Stress Testsmentioning
confidence: 99%
“…Combination testing with low-level exercise (1.7 mph, 0% grade) is recommended by the American Society of Nuclear Cardiology practice guidelines based on data that has shown that low-level exercise during adenosine MPI appears to decrease adverse effects, improve patient acceptance and image quality, and may increase the sensitivity for detecting perfusion defects 33,34. In order to further investigate the role of combination testing in patients with underlying lung disease, Garcia et al5 conducted an observational study of 116 unselected patients with mild/moderate COPD (n=67) or asthma (n=49) who underwent pharmacologic stress MPI with regadenoson in combination with low-level treadmill exercise. There was a higher incidence of dyspnea in COPD than in asthma patients (40.3% vs 22.4%; P <0.05), while asthma patients reported more headache and feeling hot (6% vs 18.4% and 10.4% vs 26.5%, respectively; P <0.05).…”
Section: Safety and Tolerability Of Regadenoson In Copd Patientsmentioning
confidence: 99%
“…There was a higher incidence of dyspnea in COPD than in asthma patients (40.3% vs 22.4%; P <0.05), while asthma patients reported more headache and feeling hot (6% vs 18.4% and 10.4% vs 26.5%, respectively; P <0.05). Adverse events were self-limited, except in three patients who suffered persistent dyspnea (2 of 67 COPD patients; 1 of 49 asthma patients) requiring theophylline administration 5. Of note, the inclusion of COPD or asthma patients was based on medical history, and patients with severe COPD/asthma or active bronchoconstriction based on physical exam were excluded.…”
Section: Safety and Tolerability Of Regadenoson In Copd Patientsmentioning
confidence: 99%
See 1 more Smart Citation